INFLUENCE OF ALLELIC VARIANTS OF PRO-INFLAMMATORY IL1B, IL17, TNF AND ANTI-INFLAMMATORY IL10 CYTOKINE GENES ON THE SEVERITY OF GINGIVITIS IN CHILDREN UNDERGOING ORTHODONTIC TREATMENT - Adamiv, S.S.; Dienga, A.E.; Verbytska, T.H.; Shnaider, S.A.; Skyba, V.Ya.; Kordonets, O.L.; Jenča, A. (World of Medicine and Biology, 2023)
The study is devoted to determining the effect of allelic variants of pro-inflammatory IL1B, IL17, TNF and anti-inflammatory IL10 cytokine genes on the severity of gingivitis in children undergoing orthodontic treatment. The study involved 18 children undergoing orthodontic treatment with varying degrees of severity of gingivitis. Dental examination was carried out in a dental office. The data presented in the paper on the effect of genetic polymorphisms of cytokine genes on the severity of gingivitis in children undergoing orthodontic treatment allows timely identification of potential genetic risk groups for inflammatory periodontal diseases for prevention and therapy, taking into account the individual characteristics of the patient.
Keywords: gingivitis; oral health; genetic polymorphism; children; polymerase chain reaction